2020
DOI: 10.1097/brs.0000000000003759
|View full text |Cite
|
Sign up to set email alerts
|

Do Preoperative Epidural Steroid Injections Increase the Risk of Infection After Lumbar Spine Surgery?

Abstract: Study Design. Retrospective study. Objective. To elucidate an association between preoperative lumbar epidural corticosteroid injections (ESI) and infection after lumbar spine surgery. Summary of Background Data. ESI may provide diagnostic and therapeutic benefit; however, concern exists regarding whether preoperative ESI may increase risk of postoperative infection. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…This association was noted to be stronger for fusion surgery (OR, 2.67; 95% CI, 2.12-3.35) and nonsignificant for decompression surgery (OR, 2.04; 95% CI, 0.96-4.34) on subgroup analysis. Similar results have been reported by Singla et al [9] (OR, 2.59; 95% CI, 2.01-3.34), Kreitz Kreitz et al [12] has presented separate data analysis for decompression and fusion surgery, which was used separately as Kreitz (D) and Kreitz (F), respectively in this study. LSSI can directly inoculate bacteria/organisms from skin flora, especially when the proper sterile precautions have not been taken [6,27].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This association was noted to be stronger for fusion surgery (OR, 2.67; 95% CI, 2.12-3.35) and nonsignificant for decompression surgery (OR, 2.04; 95% CI, 0.96-4.34) on subgroup analysis. Similar results have been reported by Singla et al [9] (OR, 2.59; 95% CI, 2.01-3.34), Kreitz Kreitz et al [12] has presented separate data analysis for decompression and fusion surgery, which was used separately as Kreitz (D) and Kreitz (F), respectively in this study. LSSI can directly inoculate bacteria/organisms from skin flora, especially when the proper sterile precautions have not been taken [6,27].…”
Section: Discussionsupporting
confidence: 87%
“…Nine studies met the inclusion criteria after following the PRISMA protocol, as shown in Fig. 1 [8,9,[11][12][13][14][15]19,20]. Two studies have used the same database with overlapping years [8,11].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations